An organic, threshold voltage based, all PMOS, voltage reference generator for flexible sensor tags. (28th December 2021) - Azimi, Mohammad; Habibi, Mehdi; Karimi-Alavijeh, Hamidreza
Abstract: The developments and advances achieved in organic semiconductors have promised lower costs for integrated circuit production and also fabrication of electronic circuits using printed technology on unconventional substrates such as plastic, clothing, and even skin. An important building block essential to most electronic circuits is a voltage, process, and temperature independent potential generator which can be used to bias amplifiers and produce a fixed reference for sensor devices. The generation of a voltage reference is also important for voltage regulators. Currently, most reported organic integrated circuits use only p-type OFETs in their circuits due to simpler fabrication procedures. Furthermore, air stable p-type organic semiconductors such as pentacene and CuPc are well characterized. In this paper, a low power two stage all PMOS voltage reference generator is proposed. Since properties such as threshold voltage value and device aging are dependent on the OFET structure, the type of device chosen for this purpose will have a direct impact on the circuit performance. Three different types of OFETs with silver, copper, and gold drain/source electrodes are studied in this work. Performance factors such as line sensitivity (LS), temperature coefficient (TC), power consumption, time constant, and output drifts of the fabricated integrated circuits are measured and reported to verify the characteristics of the proposed circuits. It is shown that the drain/source metal choice affects the threshold voltage dependent output potential of the reference generators.